Factors Of Self-Professional Development Of School Teachers - A.G‘.Suyunov. (Genius Publishing Group, 2023)
In this article, the factors of self-professional development of school teachers are widely covered. In addition, the professional and technological factors of the teacher are listed socio-economic factors.
Keywords: self-professional development; personal professional development; continuous professional growth